THE USE OF PHYSICAL SETTING PREFERENCE BY GENERATION Z IN PUBLIC OPEN SPACE, CASE STUDY: YOGYAKARTA 0 KILOMETER POINT - Alif Faricha Almadina; Syam Rachma Marcillia (Lakar: Jurnal Arsitektur, 2023)
Open public space is one of the preferred destinations for Z-Generation. Public space is composed of an arrangement of physical elements to accommodate user activities in it. Physical elements within the open public space establish become a physical setting that is used for activities by Z-generation. This study aims to determine preferences of physical setting utilizations for Z-Generation in open public spaces. The research is located at Titik 0 km Yogyakarta. Titik 0 km Yogyakarta is one of the open public spaces in central Yogyakarta that become young people's favorite destination. The research method uses questionnaires and interviews with a purposive sampling technique. Results of the study showed that Z-Generation tends to choose activities with friends while at Titik 0 km Yogyakarta. Activities that tend to be carried out by Z-Generation include relaxing, taking pictures, and chatting at Point 0 km Yogyakarta. Seating elements such as benches and stools, are used for chatting and relaxing. The vegetation frames, which is planter edge, is used for relaxing. Bollard elements are utilized for photo activities. Sports activities are most suitable for circulation path settings in the spacious flat roads. Elements of physical settings that tend to be used for activities are elements that provide comfort and privacy, as well as increase aesthetic value. Aspects of comfort and privacy for social activities and aesthetic aspects for recreational activities.